2003
DOI: 10.1073/pnas.1930781100
|View full text |Cite
|
Sign up to set email alerts
|

A natural mutation in the Tyk2 pseudokinase domain underlies altered susceptibility of B10.Q/J mice to infection and autoimmunity

Abstract: The B10.Q͞J strain of mice was serendipitously discovered to be highly susceptible to infection by the intracellular protozoan parasite, Toxoplasma gondii but markedly resistant to induction of autoimmune arthritis. We have previously shown that the B10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
94
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 48 publications
7
94
1
Order By: Relevance
“…We further found that Tyk2 is critical for IL-17 production by ␥␦ T cells and protection against E. coli infection in vivo. There have been reports showing involvement of Tyk2 in IL-23-mediated signaling using Tyk2-deficient mice, including an impaired STAT3 phosphorylation of ConAstimulated T cells (13) and an impaired IFN-␥ production of dendritic cells (23). However, to our knowledge, this is the first report demonstrating an importance of Tyk2 in IL-23-mediated signaling for IL-17 production.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…We further found that Tyk2 is critical for IL-17 production by ␥␦ T cells and protection against E. coli infection in vivo. There have been reports showing involvement of Tyk2 in IL-23-mediated signaling using Tyk2-deficient mice, including an impaired STAT3 phosphorylation of ConAstimulated T cells (13) and an impaired IFN-␥ production of dendritic cells (23). However, to our knowledge, this is the first report demonstrating an importance of Tyk2 in IL-23-mediated signaling for IL-17 production.…”
Section: Discussionmentioning
confidence: 72%
“…As Tyk2 is recruited to IL-12R␤1 (9), IL-23-mediated signaling also likely involves Tyk2. In fact, an impaired IL-23-induced phosphorylation of STAT3 was shown in Tyk2-deficient T cells (13), suggesting an importance of Tyk2 for IL-23-mediated signaling for IL-17 production.…”
mentioning
confidence: 99%
“…Recently, pseudokinases have emerged as key regulatory effectors in metazoan signal transduction (35), particularly in mammalian immune signaling (36,37). Although it is difficult to determine the specific role of a catalytically inactive protein, other pseudokinases have been shown to act as molecular scaffolds (38)(39)(40) and thereby, coordinate signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Tyk-2 is also involved in the function of several other cytokines that have been reported to be elevated in SLE patients, such as IL-6 and IL-10 (56). The importance of Tyk-2 in autoimmunity is further supported by the observation that Tyk-2-deficient mice are resistant to experimental arthritis (57). IRF-5, in contrast, is important for induction of IFN␣ production by viral infections and TLR-7/8 agonists and is constitutively expressed in NIPCs/PDCs (58,59).…”
Section: Introductionmentioning
confidence: 94%